High-radiance light sources with LED-pumped luminescent concentrators applied to pump Nd:YAG passively Q-switched laser. (1st November 2017) - Pichon, P.; Barbet, A.; Blengino, D.; Legavre, P.; Gallinelli, T.; Druon, F.; Blanchot, J.-P.; Balembois, F.; Forget, S.; Chénais, S.; Georges, P.
Highlights: High-radiance LEDs pump Ce:YAG luminescent concentrators are described. First Q-switched indirectly LED-pumped Nd:YAG laser at room temperature. First longitudinal pumping with a LED concentrator. Abstract: By power scaling of LEDs pump concentrators we demonstrated a visible light source (centered at 550 nm) producing 294 W with a radiance of 668 W/cm 2 /sr in the air. Using more than 1100 LEDs, this setup represents one order of magnitude improvement in terms of output power and brightest of LED pump concentrator ever reported. We pushed further the concept of low cost high brightness light source using this concentrator to pump a very simple Nd:YAG laser in free running mode and in passively Q-switched regime using a Cr:YAG saturable absorber. Output energies up to 263 µJ with a pulse duration of 33 ns have been obtained at 1064 nm, leading to a peak power of 8 kW in a TEM00 mode.